Synthesis and characterization of cellulose nanocrystal derived from paper as nanofiller for polymer insulation materials - Nurul Shafiqah Amirah, Badi; Mohamad Zul Hilmey, Makmud; Chin, Se Mun; Zuhair, Jamain; Jahimin, Asik; Khairatun Najwa, Mohd Amin (Elsevier Ltd, 2024)
The synthesis and characterization of cellulose nanocrystal by utilizing filter paper as the source of material deserves to be an advanced approach. Nanocellulose has received enormous attention due to its unique properties. Being the most abundant organic polymer on earth, nanocellulose is the most suitable candidate for alternative replacement of petroleum-based products. The cellulose was extracted from filter paper by chemical processes involved alkali treatment, bleaching treatment, and acid hydrolysis. Cellulose nanocrystal has been characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and Electrical Impedance Spectroscopy (EIS). The dielectric permittivity of the prepared CNC have been investigated in the different temperatures. The nanofiller CNC exhibits a higher real permittivity value at elevated temperatures (60 °C) in the low-frequency region. At high-frequency region, the real permittivity is independent on temperature. In brief, the studies point to the application potential of CNC for future insulation materials.